Differential diagnosis of smooth muscle tumors utilizing p53, pTEN and Ki-67 expression with estrogen and progesterone receptors - (:unkn) unknown (KARGER, 2005)
Background/Aim: To investigate the expression and value for diagnosis of the genes, p53 and pTEN, the protein, Ki-67, and the receptors, estrogen and progesterone, in differentiating smooth muscle tumors of the uterus. Material and Method: Seventeen samples of leiomyosarcoma, 2 smooth muscle tumors with uncertain malignant potential ( STUMP), 9 atypical myomas and 15 leiomyomas were stained immunohistochemically. The chi(2) test was used for the statistical analysis of the data. Results: The malignant side of the spectrum was strongly stained for Ki-67 and p53 while uniformly decreasing toward the benign tumors. The results were found to be statistically significant ( p < 0.0001). The staining for progesterone receptor was also statistically significant, but the tumors that were considered benign, such as leiomyoma and atypical myoma, were the ones strongly stained ( p = 0.005). The expression of estrogen receptor was significant in these tumors, but the p value was very close to the cut-off value ( p = 0.07). As the degree of differentiation of the tumor increased, the trend showed stronger staining for estrogen receptor. However, no difference was detected in the staining properties of the tumors for pTEN ( p = 0.2457). Conclusion: The expression of Ki-67, p53 and progesterone receptors is promising in immunodifferentiation of smooth muscle tumors of the uterus with malignant potential. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: p53; pTEN; Ki-67; estrogen receptor; progesterone receptor; smooth muscle tumors; UTERINE; LEIOMYOSARCOMA; PROTEIN